2014
DOI: 10.1007/s10620-014-3245-9
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Colorectal Adenomas in Patients Under 45 Years of Age Are Mostly Sporadic

Abstract: Background The presence of advanced adenomas in younger individuals is a criterion for Lynch syndrome (LS). However, the utility of screening advanced adenomas for loss of mismatch repair (MMR) protein expression to identify suspected LS remains unclear. Aims Determine the prevalence of MMR defects to understand whether these patients harbor a defined genetic risk for CRC. Methods The study cohort included adult patients ≤45 years of age with advanced adenomas (villous histology, ≥1 cm in diameter, ≥3 poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…However, screening of unselected adenomas has not been shown to be an effective strategy for identifying novel cases of Lynch syndrome. 37,38,41 Similarly, the current study found only 1 patient, less than 1% of patients with EIN, who demonstrated a pattern of MMR deficiency potentially associated with Lynch syndrome. Although loss of MMR protein expression has been observed in premalignant lesions in patients with Lynch syndrome, 7,2528 it seems to be a relatively infrequent event in an unselected population of patients with EIN.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…However, screening of unselected adenomas has not been shown to be an effective strategy for identifying novel cases of Lynch syndrome. 37,38,41 Similarly, the current study found only 1 patient, less than 1% of patients with EIN, who demonstrated a pattern of MMR deficiency potentially associated with Lynch syndrome. Although loss of MMR protein expression has been observed in premalignant lesions in patients with Lynch syndrome, 7,2528 it seems to be a relatively infrequent event in an unselected population of patients with EIN.…”
Section: Discussionsupporting
confidence: 48%
“…3641 Shia et al 36 suggested that evaluating adenomas with IHC might be productive in a clinically defined subset of patients, such as those with a strong family history of colorectal cancer. However, screening of unselected adenomas has not been shown to be an effective strategy for identifying novel cases of Lynch syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Kushnir et al . reported that advanced adenoma developed in 10.5% of young patients (<45 years) after a mean 3.3 years . Yamaji et al .…”
Section: Discussionmentioning
confidence: 99%
“…As young adults with CRC often have more aggressive tumor characteristics and show different prognosis compared with older adults, advanced adenoma in young patients may have different characteristics and prognosis compared with those in older patients. However, only a few studies have reported the prognosis of young patients after removing advanced adenoma detected at index colonoscopy . Thus, we aimed to investigate the risk of developing advanced colorectal neoplasm in young patients after removing high‐risk adenoma detected at index colonoscopy compared with that in older patients.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with LS do not typically present with a polyposis; the development of progressive dMMR appears more important in adenoma progression than in initiation. In a study of 66 advanced adenomas (inclusion criteria of adenoma 1 cm, villous architecture, and/or 3 polyps) in 10 Thus, although we do not typically screen adenomas for LS, in patients with a compelling family history in which no other cancer tissue is available, we will perform MMR IHC. In ten studies examining 424 conventional adenomas in LS patients, the overall frequency of abnormal MMR IHC is 75%, ranging from 50 to 90% in individual studies.…”
Section: Mismatch Repair Deficiency In Colorectal Adenomasmentioning
confidence: 99%